PENGARUH FEE AUDIT, KOMPETENSI AUDITOR, DAN PERUBAHAN KEWEWANGAN TERHADAP MOTIVASI AUDITOR (Studi Empiris Pada Auditor Kantor Akuntan Publik Di Jawa Tengah Yang Terdaftar Di BPK RI) - Septyan Candra Wijaya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
This study aims to determine the effect of audit fee, auditor competence, and authoritative changes on auditor motivation. 100 samples of Central Java Public Accounting Firms registered in BPK RI are acquired through convenience sampling. The data are collected from questionnaire survey resulting in 57 auditors as the respondents, and analyzed by Partial Least Square (PLS) model utilizing WarpPLS v.7 software. The result of this study indicate that auditor competence and authoritative changes have positive affect on auditor motivation, while audit fee has negative effect on auditor motivation. Good auditor competence and authoritative changes determine the auditor motivation, and the later can also be achallenge for auditors to audit in the government sector.Keyword: audit fee, auditor competence, authoritative change, and auditor motivation.